Lewis-Acid-Catalyzed (3+2) Annulation of 2-Indolylmethanols with Propargylic Alcohols to Access Cyclopenta[b]indoles - Teng-Fei Wu; Zhao-Jie Fu; Yi-Rui Zhang; Zong-Wang Qiu; Bao Qiong Li; Shao-Shuai Chen; Han-Peng Pan; Ai-Jun Ma; Xiang-Zhi Zhang (Molecules, 2024)
Herein, a Sc(OTf)3-catalyzed (3+2) annulation of 2-indolylmethanols with propargylic alcohols is reported. The reaction proceeds via a Friedel–Crafts-type allenylation/5-exo-annulation cascade. In the reaction, 2-indolylmethanol is used as a three-carbon synthon, and propargyl alcohol is used as a two-carbon synthon. This method provides a direct and high-yield pathway for synthetically useful cyclopenta[b]indoles. In general, the method features easily accessible substrates with broad scope and generality, the formation of multiple bonds with high efficiency, and easy scale-up.